Ultrasound Detects Early Involvement and Correlates with other Techniques in SSc - Lederman, Lynne (MD Conference Express, 2014)
Systemic sclerosis (SSc) is characterized by increased dermal thickness; the severity and extent of skin involvement are used to establish the diagnosis and subclassify the disease. The modified Rodnan skin score is a validated method to evaluate skin involvement in SSc, and it is based on manual palpation of 17 areas of the skin. This article discusses detection of subclinical diffuse dermal involvement by high-frequency ultrasound in patients with limited cutaneous SSc.